No hay tal cosa como la sociedad: cultura neoliberal y la antropología radical de Marilyn Strathern; There’s no such thing as a society: neoliberal culture and Marilyn Strathern’s radical anthropology - Zolla Márquez, Emiliano (Universidad Autónoma Metropolitana, 2020)
Este artículo explora la relación entre el trabajo etnográfico y la cultura de las sociedades de las que provienen los antropólogos. En concreto, el texto revisa la forma en que el pensamiento neoliberal, impulsado por Margaret Thatcher, impactó la forma de concebir y practicar la antropología en el contexto del Reino Unido. Se sostiene que el neoliberalismo resquebrajó los fundamentos del funcionalismo y otras formas clásicas de la teoría antropológica. Al mismo tiempo, se plantea que la obra de Marilyn Strathern constituye una respuesta a la crisis conceptual abierta por el neoliberalismo a través de una crítica etnográfica de las nociones occidentales de sociedad e individuo.; This article explores the relationship between ethno- graphic work and the culture of those societies from which anthropologists come from. Specifically, the text delves into the way in which neoliberal thinking and politics during Margaret Thatcher’s era influenced ways of thinking and practicing anthropology in Great Britain by disturbing the foundations of functionalism as well as other classic anthropological theories. At the same time, the article describes the way in which Marilyn Strathern’s thought challenges the theoretical crisis opened by neoliberalism, by means of an ethnographic critique of central Western concepts such as society or individual.